Effect of Feed and Air Temperature on Optimum Egg Size and Profits During Phase 1 of Bovans White Hens - Roland, D.A.; Bryant, M. (International Journal of Poultry Science, 2008)
Two experiments were conducted to determine the most economical protein and lysine levels to feed laying hens during Phase I (weeks 21-36) of the laying cycle in order to optimize egg weight and profits when hens were exposed to warm (25.6 °C Average in Exp. 1) and cool temperatures (20.0 °C average in Exp. 2). In both experiments, nine hundred sixty 21-weeks old hens were randomly divided into six groups of 160 hens per group and fed one of six diets. Diets were formulated based on protein and lysine. Three diets formulated on protein contained 17.00, 18.70 and 20.80% protein and 0.90, 1.02 and 1.17% lysine, respectively. Three diets formulated based on lysine contained 0.75, 0.83 and 0.92% lysine and 14.98, 16.19 and 17.34% protein, respectively. Response criteria were egg production, feed consumption and egg weight. Neither diet nor method of formulation had an effect (p>0.05) on any response criteria other than egg weight in Exp. 1 and Exp. 2. In both experiments, egg weight increased (p<0.05) as the Lysine (or protein) content increased. Using an economic analysis with egg and feed prices at the time of the study, Bovans White hens required 1,076 mg lysine, 750 mg total sulphur amino acids (TSAA), 19.1 g protein and 264 kcal ME/hen/d for optimum profits during Phase I under warm conditions and 1,100 mg Lysine, 789 mg TSAA, 20.22 g protein and 310 kcal ME/hen/d during Phase I for maximum profits when kept under cool temperatures. Because feed and egg prices vary, there can be no fixed lysine (protein) requirement for optimal profit.